2021
DOI: 10.3389/fnut.2021.718356
|View full text |Cite|
|
Sign up to set email alerts
|

Inflammatory and Microbiota-Related Regulation of the Intestinal Epithelial Barrier

Abstract: The intestinal epithelial barrier (IEB) is one of the largest interfaces between the environment and the internal milieu of the body. It is essential to limit the passage of harmful antigens and microorganisms and, on the other side, to assure the absorption of nutrients and water. The maintenance of this delicate equilibrium is tightly regulated as it is essential for human homeostasis. Luminal solutes and ions can pass across the IEB via two main routes: the transcellular pathway or the paracellular pathway.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
113
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(149 citation statements)
references
References 372 publications
0
113
0
8
Order By: Relevance
“…Although the severe outcomes of induced colitis were marked, the more subtle impact that loss of Zbtb20 in T cells had on the maintenance of the intestinal epithelial barrier (IEB) integrity may ultimately be of greater importance. The IEB has multiple functions including preventing the release of potentially harmful pathogens and antigens while also directly aiding in the absorption of nutrients and water (53). Hence, IEB integrity is associated with a broad range of diseases including inflammatory bowel disease (IBD), irritable bowel syndrome, and even Celiac disease (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…Although the severe outcomes of induced colitis were marked, the more subtle impact that loss of Zbtb20 in T cells had on the maintenance of the intestinal epithelial barrier (IEB) integrity may ultimately be of greater importance. The IEB has multiple functions including preventing the release of potentially harmful pathogens and antigens while also directly aiding in the absorption of nutrients and water (53). Hence, IEB integrity is associated with a broad range of diseases including inflammatory bowel disease (IBD), irritable bowel syndrome, and even Celiac disease (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal epithelial barrier acts as the first line of defense by avoiding the entrance of antigens and pathogens ( Barbara et al, 2021 ). The alteration of the gut microbiota is the most important factor that disrupts the integrity of the intestinal epithelial barrier, leading to intestinal inflammation and diseases ( Gareau et al, 2010 ).…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 99%
“…As for the physical barrier, in vitro and in vivo experiments have demonstrated that EVs released by E. coli Nissle 1917 can mediate anti-inflammatory effects and protect the intestinal epithelial barrier function ( Alvarez et al, 2016 ; FĂĄbrega et al, 2016 , 2017 ). A key role in the maintenance of intestinal epithelial barrier integrity is played by tight junctions, which are composed of a network of proteins that regulate paracellular permeability, such as claudins, zonula occludens (ZO) and occludin ( Barbara et al, 2021 ). EVs released by E. coli Nissle 1917 have been shown to upregulate ZO-1 and claudin-14, downregulate claudin-2 (a gene that codes for a leaky protein), and in turn improve epithelial barrier function in an in vitro intestinal epithelium models (T-84 and Caco-2 cell lines) ( Alvarez et al, 2016 ).…”
Section: Extracellular Vesicles From Probiotic Bacteria and Infectiou...mentioning
confidence: 99%
See 1 more Smart Citation
“…IBS is a multifactorial disorder with a complex and not completely understood pathophysiology [31] . Previously, IBS has been mainly considered a psychosomatic disorder in which psychosocial factors, including stress, anxiety, and depression, markedly contributed to altered motility and visceral hypersensitivity [32] . IBS is now considered a disorder of the gut-brain axis (DGBI) characterized by a complex interplay between peripheral and central factors, including genetic predisposition, alterations in gastrointestinal sensory-motor function, intestinal dysbiosis, increased intestinal permeability, mucosal lowgrade inflammation and immune activation, neuroendocrine abnormalities, food sensitivity, and psychosocial factors [Figure 1] [11,31,33] .…”
Section: Pathophysiologymentioning
confidence: 99%